The centered mind : what the science of working memory shows us about the nature of human thought - Peter Carruthers (Oxford University Press, 2015)
This book offers a new view of the nature and causal determinants of both reflective thinking and, more generally, the stream of consciousness. Peter Carruthers argues that conscious thought is always sensory-based, relying on the resources of the working-memory system. This system has been much studied by cognitive scientists. It enables sensory images to be sustained and manipulated through attentional signals directed at midlevel sensory areas of the brain. When abstract conceptual representations are bound into these images, we consciously experience ourselves as making judgments or arriving at decisions. Thus one might hear oneself as judging, in inner speech, that it is time to go home, for example. However, our amodal (non-sensory) propositional attitudes are never actually among the contents of this stream of conscious reflection. Our beliefs, goals, and decisions are only ever active in the background of consciousness, working behind the scenes to select the sensory-based imagery that occurs in working memory. They are never themselves conscious.